Penggunaan Lembar Kerja Siswa dalam Proses Pembelajaran di TK X Cihampelas - Alisya M Rahmawati; Huriah Rachmah (Jurnal Riset Pendidikan Guru Paud, 2022)
Abstract. Student worksheets are learning media that are quite often found in early childhood education institutions. X Cihampelas Kindergarten uses student worksheets because it is effective in attracting children’s learning interest. Based on this background, the problems in this study are formulated as follows: (1) How is learning planning using student worksheets media at X Cihampelas Kindergarten? (2) How is the implementation of learning using student worksheets media in X Cihampelas Kindergarten? (3) How is the evalution of learning by using student worksheets media at X Cihampelas Kindergarten? (4) What are the advantages and disadvantages of using student worksheets in learning at X Ciampelas Kindergaten?. The research method used in this research Is descriptive qualitative. The data colletion techniques used were observation, interviews, and documentation studies. The results of this study obtained an illustration of the use of student worksheets in the learning process. The use of student worksheets in learning only applies the principles of learning that are interesting and fun, as well as thematic, and can effect aspects of children’s development including aspects of reigiousvalues and moral, fine motor, cognitive, language, and socio-emotional. Abstrak. Lembar Kerja Siswa (LKS) adalah media pembelajaran yang cukup sering ditemukan di lembaga pendidikan anak usia dini. TK X Cihampelas menggunakan LKS karena efektif dalam menarik minat belajar anak. Berdasarkan latar belakang tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana perencanaan pembelajaran dengan menggunakan media LKS di TK X Cihampelas? (2) Bagaimana pelaksanaan pembelajaran dengan menggunakan media LKS di TK X Cihampelas? (3) Bagaimana evaluasi pembelajaran dengan menggunakan media LKS di TK X Cihampelas? (4) Bagaimana kelebihan dan kelemahan penggunaan LKS dalam proses pembelajaran di TK X Cihampelas? Metode penelitian yang digunakan pada penelitian ini adalah kualitatif deskriptif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan studi dokumentasi. Hasil dari penelitian ini adalah didapatkan gambaran tentang penggunaan Lembar Kerja Siswa (LKS) dalam proses pembelajaran. Penggunaan media LKS dalam pembelajaran hanya menerapkan prinsip pembelajaran yang menarik dan menyenangkan, tematik, serta dapat mempengaruhi aspek-aspek perkembangan anak di antaranya adalah aspek nilai agama dan moral, motorik halus, kognitif, bahasa, dan sosial-emosional.